Maximum Power Point Tracking Solar Charge Controller Based on Internet of Things with Smartphone Display - Ushalli, Muhammad Ajriy; Yulkifli, Y; Mairizwan, M; Anshari, Rio (PILLAR OF PHYSICS, 2023)
Electrical energy is a very important thing in life, but the main source at this time is still using limited materials. The solution to this problem requires renewable energy as an alternative source. This research discusses solutions with the use of solar cells. Harvesting of solar cell power is carried out using a Maximum Power Point Tracking (MPPT) based on Internet of Things (IoT). This research is classified as development research. The purpose of this research is the performance specification and design specifications. The data obtained in this study are comparisons of MPPT data and not using MPPT, and also accuracy and precision data of the instrument. Data collection was carried out on August 7, 2022 at 10.00 WIB - 16.00 WIB. In the study, it was found that the power harvested using the MPPT system was much better than without using the MPPT system. The system performance specifications are built with various electronic components and microcontrollers, all components are included in a box measuring 20cm x 15cm x 9cm. design specifications obtained an good data with MPPT based on IoT. The value of accuracy instrument is obtained 93,87% and the precision value of the instrument is obtained 94,944%. And also obtained good data transfer capabilities from the instrument, so that data transfer can be done continuously. with the method used, the research went well and in line with expectations